Infliximab-induced psoriasis during therapy for Crohn's disease - Steinwurz, Flavio; Denadai, Rafael [UNESP]; Saad-Hossne, Rogerio [UNESP]; Queiroz, Maria Luiza; Teixeira, Fabio Vieira [UNESP]; Romiti, Ricardo (Elsevier B.V., 2012)
Although therapy with tumor necrosis factor-alpha inhibitors (anti-TNF) provides beneficial effects in different immune inflammatory disorders, paradoxical cases of anti-THE-induced psoriasis have increasingly been reported, mostly in the setting of rheumatologic diseases. To date, less than 50 cases of infliximab-induced psoriasis in inflammatory bowel disease patients have been described. The present report was aimed at describing two new cases of infliximab-induced psoriasis during therapy for Crohn's disease and at carrying out a review on this intriguing phenomenon. (C) 2011 European Crohn's and Colitis Organisation. Published by Elsevier B.V. All rights reserved.
Keywords: Biological therapy; Crohn's disease; Infliximab; Psoriasis; Tumor necrosis factor-alpha inhibitors